Asymmetrical federalism and anti-federal sentiment in Malaysia : the Sabah experience - Mohammad Azziyadi Ismail,; Mohammad Agus Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Federalism is a system of fair and orderly power sharing between the state and federal governments. However, in the case of the Federation of Malaysia, this division is unbalanced and asymmetrical, owing to the fact that Sabah and Sarawak have been given more privileges than other states in Malaya as a condition to join the Federation of Malaysia during its formation on 16 September 1963. These terms were proposed by the Intergovernmental Committee and included in the Malaysia Agreement 1963 (MA63), which was signed on July 9, 1963, in London by the United Kingdom, the Federation of Malaya (Malaya), North Borneo (Sabah), Sarawak, and Singapore. Despite the fact that MA63 and the 20-point Agreement grant Sabah unique privileges, the state has long struggled with federalism issues, giving rise to anti-federal sentiments. Using the concept of asymmetrical federalism as a tool of analysis, this study examines the issues of asymmetrical federalism responsible for the anti-federal sentiment in Sabah. Interviews were used to collect primary data, while sources including books, journals, newspapers and online news were mined for secondary data in this qualitative study. Oil royalties, unequal development between Sabah and the Peninsula, immigration and security threats, Sabah's regional status within Malaysia and Borneonisation were found to be the five main issues that prompted Sabahans to be dissatisfied with the implementation of asymmetrical federalism. The failure of the Sabah and federal governments to address these issues has contributed to the birth of anti-federal sentiment in Sabah.